The Impact of Complication Timing on the Outcomes of Implant-based Breast Reconstruction - Tahera Alnaseri, MPH; Shamit Prabhu, MD, MS; Lexy Anderson, BA; Lorna Kwan, MPH; Maral Demirjian, MPH; Alvin Kwok, MD; Christopher Reid, MD; Scott Hollenbeck, MD; Michael R. DeLong, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. The National Surgical Quality Improvement Program (NSQIP) database provides an important resource for determining complication rates and risk factors for surgical procedures. However, NSQIP is limited to 30-day follow-up, and it is unclear whether this is reliable for evaluating prosthetic breast reconstruction outcomes. Methods:. A single-institution, cross-sectional, retrospective review was performed for patients undergoing mastectomy with immediate, prepectoral tissue expander reconstruction. Timing of complications was stratified as early (within 30 days of operation) versus late (after 30 days). Categorical variables were compared using χ2 (or Fisher exact) tests, and continuous variables were analyzed using Kruskal-Wallis or Wilcoxon rank-sum tests. Results:. There were 301 patients (509 reconstructed breasts) included with a median follow-up time of 11 months. Of them, 176 patients (58%) experienced a postoperative complication—140 patients (47%) experienced an early complication and 36 patients (12%) experienced a late complication. Patients with late complications had a significantly higher rate of reconstructive failure compared with the early complication group (17% versus 10%; P = 0.001) and were more likely to require a flap (28% versus 7%; P = 0.001) for final reconstruction. Revision surgery rates after final implant placement were higher in the late complication group (36% versus 64%; P = 0.285). Conclusions:. Late complications after prepectoral breast reconstruction have a more prominent impact on reconstructive failure and revisions than early complications. This finding may inform strategies to revise national databases such as NSQIP to include more detailed information and longer capture periods.